2010
DOI: 10.1128/aem.02738-09
|View full text |Cite
|
Sign up to set email alerts
|

AiiM, a Novel Class of N -Acylhomoserine Lactonase from the Leaf-Associated Bacterium Microbacterium testaceum

Abstract: N-Acylhomoserine lactones (AHLs) are used as quorum-sensing signal molecules by many Gram-negative bacteria. We have reported that Microbacterium testaceum StLB037, which was isolated from the leaf surface of potato, has AHL-degrading activity. In this study, we cloned the aiiM gene from the genomic library of StLB037, which has AHL-degrading activity and shows high homology with the ␣/␤ hydrolase fold family from Actinobacteria. Purified AiiM as a maltose binding fusion protein showed high degrading activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 33 publications
1
97
2
Order By: Relevance
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
“…Metagenomic analyses faciliated the discovery of QlcA, BipB01, BipB04, BipB05, and BipB07 (68,74,75), and screens for AHL-degrading bacteria led to the identification of QsdA of Rhodococcus erythropolis strain W2 (70), AiiM of Microbacterium testaceum (71), AidH of Ochrobactrium sp. strain T63 (72), and QsdH of Pseudoalteromonas byunsanensis strain 1A01261 (73).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…This is similar to the AHL degradation pattern for AHL lactonase (AiiM) from Microbacterium testaceum. 25) In addition, narrowing the window of variation, the AHLdegrading activity was highest against OdDHL and lowest against OHHL, indicating that the 3-oxo group of AHL substrates was not required for interaction between the lactonase and an AHL substrate. 24) In contrast, AiiM from M. testaceum degraded better against the 3-oxo substituted AHL substrates than the unsubstituted type.…”
Section: Discussionmentioning
confidence: 99%
“…24) In contrast, AiiM from M. testaceum degraded better against the 3-oxo substituted AHL substrates than the unsubstituted type. 25) No AHL-degrading activity of G. caldoxylosilyticus YS-8 was apparent with the cell-free extract treated by either boiling or proteinase K, suggesting that the AHL degradation by G. caldosylosilyticus YS-8 resulted from an enzymatic inactivation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65][66][67][68][69][70][71][72][73] Furthermore, AHLinactivating Gram-positive bacteria within the Arthrobacter, Bacillus, Microbacterium, Nocardioides, Rhodococcus, and Streptomyces genera are also found to have the ability to inactivate AHLs, suggesting that phylogenetically diverse bacteria can quench the AHL-based QS. 66,68,[74][75][76][77][78] AHL-inactivating enzymes have been found in AHL-inactivating bacteria, and these enzymes can be divided into three representative families: AHL-lactonases, AHL-acylases, and AHL-oxidoreductases (Fig. 6).…”
Section: Metagenomic Screening For Quorum-sensing Inhibitorsmentioning
confidence: 99%